Black mothers' recreational choices for their children: a critical race theory story. Issue 5 (20th October 2021) - Hallmon, Augustus; Anaza, Emeka; Sandoval, Alexandra; Fernandez, Mariela
ABSTRACT: Using critical race theory (CRT), this paper examined how race influenced Black mothers' recreational choices for their children. In presenting the findings, this paper used storytelling inspired by interviews conducted with single Black mothers living in a small midwestern U. S. town. Black mothers hoped to prepare their children to successfully navigate society through recreation opportunities, but often found limited community-based recreational opportunities in their neighbourhood. Mothers felt the need to protect their children from programs that perpetuated racist stereotypes, tokenism, and discrimination against their children and/or Blacks in general. Some mothers felt that stereotypes and discrimination were embedded in programmatic offerings, and tokenism was used in recreational programs where many of the staff and children were White. In telling the story of single Black mothers' efforts to find appropriate programs for their children, this paper highlights the structural racism still embedded in today's community-based recreational offerings.